Setting scientific names at all taxonomic ranks in italics facilitates their quick recognition in scientific papers - Marco Thines; Takayuki Aoki; Pedro W. Crous; Kevin D. Hyde; Robert Lücking; Elaine Malosso; Tom W. May; Andrew N. Miller; Scott A. Redhead; Andrey M. Yurkov; David L. Hawksworth (IMA Fungus)
Abstract It is common practice in scientific journals to print genus and species names in italics. This is not only historical as species names were traditionally derived from Greek or Latin. Importantly, it also facilitates the rapid recognition of genus and species names when skimming through manuscripts. However, names above the genus level are not always italicized, except in some journals which have adopted this practice for all scientific names. Since scientific names treated under the various Codes of nomenclature are without exception treated as Latin, there is no reason why names above genus level should be handled differently, particularly as higher taxon names are becoming increasingly relevant in systematic and evolutionary studies and their italicization would aid the unambiguous recognition of formal scientific names distinguishing them from colloquial names. Several leading mycological and botanical journals have already adopted italics for names of all taxa regardless of rank over recent decades, as is the practice in the International Code of Nomenclature for algae, fungi, and plants, and we hereby recommend that this practice be taken up broadly in scientific journals and textbooks.